High stakes [large type] - Johansen, Iris (Grand Central Publishing Large Print, 2021)
"Logan Tanner lives the exhilarating life of a professional gambler, taking risks with nerves of steel. From casinos in Macau to Monte Carlo to Milan, he's racked up a fortune and become a living legend. But all the glitz and glamor hide a dark and violent past as an extractor--a world that comes rushing back to him when the beautiful and innocent Lara Balkon enters his life"--